Physicochemical, water, thermal and mechanical properties of cellulosed-based Kraft paper produced from five Malaysian bamboo species - H.S.N. Hawanis; R.A. Ilyas; R. Jalil; R. Ibrahim; R.A. Majid; N.H. Ab Hamid; M.N.F. Norrrahim; V.F. Knight (Carbohydrate Polymer Technologies and Applications, 2025)
This study focuses on the chemical composition, physicochemical properties, water-holding capacity, thermal behaviour, and physical and mechanical characteristics of native bamboo species in Malaysia. The species examined include Gigantochloa scortechinii (GS), Gigantochloa wrayi (GW), Gigantochloa levis (GL), Schizostachyum grande (SG), and Dendrocalamus asper (DA), chosen for their abundance and distribution in bamboo plantations. The Kraft pulping process, which utilizes alkaline treatment with sodium hydroxide and sodium sulphide at a sulphidity level of 25 %, is designed to dissolve lignin and convert bamboo into fibrous pulp suitable for papermaking. The effects of Kraft pulping were found to be beneficial to the GL bamboo species by producing the highest mechanical properties among all other bamboo species. Specifically, GL demonstrates tear index, tensile index, and number of folds values at 26.11 ± 1.79 mN.m2/g, 31.83 ± 0.09 Nm/g, and 24.87 ± 6.85, respectively. The utilization of Kraft pulping with a sulphidity of 25 % presents a promising potential for processing all five native Malaysian bamboo species into paper. This comparative analysis serves to deepen our comprehension of the effects of Kraft pulping on paper properties and provides valuable insights into harnessing bamboo fibers for sustainable pulp and paper production.